Homoseksual dalam Al-Qur`an: Studi Komparatif Penafsiran Wahbah Az-Zuhaili dan Mahmud Yunus - Hayuti Sukma Jelita; Dapit Amril (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this research is homosexuality in the Qur'an, a comparative study of the interpretation of Wahbah Az-Zuhaili and Mahmud Yunus. The purpose of this research is to find out and identify the similarities and differences in the interpretation of Az-Zuhaili's and Mahmud Yunus's interpretations of homosexuality. This type of research is library research. The method used in this study is the muqaran method by analyzing the interpretation of two figures related to homosexuality by using a comparative method. while analyzing the interpretation using the interpretation approach. Primary data sources of this study are the verses of the Koran, Al Munir's commentary by Wahbah Az-Zuhaili and Mahmud Yunus's interpretation of the Qur'an Karim. while the secondary data of this research are the results of research or original theoretical or theoretical writings, dictionaries, books, articles and journals that are relevant to this research. The results of this study conclude first, the Qur'an views homosexual behavior as fahisyah because it violates normal human nature to like the opposite sex. there is also a difference between the two mufassirs in interpreting lafadz fahisyah mufassir Wahbah Az-Zuhaili interprets it as an abomination while Mahmud Yunus interprets it as a crime. second, there are differences and similarities in the interpretation of these two commentators, namely in the punishment given by Allah, namely (Wahbah Az-Zuhaili: Allah punished the people of the prophet Lut in the form of a hail of stones and destroyed their country. Meanwhile, Mahmud Yunus interpreted Allah to punish the people of the prophet Lut in the form of rain of pebbles, a very great earthquake and destroyed their country.